Health Outcomes and Quality of Life Indices of Children Receiving Blenderized Feeds via Enteral Tube - Hron, Bridget (J Pediatr, 2019)
OBJECTIVE: To determine whether clinical and patient-reported outcomes differ in children receiving blenderized diets compared with conventional formula. STUDY DESIGN: We conducted a prospective cohort study of 70 children age 1–18 years receiving blenderized diets versus conventional formula via feeding tube. We assessed rates of hospitalization and emergency room (ER) visits at Boston Children’s Hospital in 2017; and Likert scale addressing satisfaction with feeding regimen; Pediatric Gastroesophageal Reflux Disease Symptom and Quality of Life Questionnaire (PGSQ); Pediatric Quality of Life Inventory (PedsQL), and PedsQL Gastrointestinal Symptoms Scale (GI-PedsQL). RESULTS: Participants receiving blenderized diets (N=42, 60%) did not differ in demographics or comorbid diagnoses from those receiving conventional formula (N=28, 40%). Rates of total ER visits (0.8±1.5 vs. 1.4±2.7, P = .05), total admissions (0.8±1.2 vs. 1.7±2.3, P=0.01) and respiratory admissions (0.2±0.5 vs. 0.6±0.8, P=0.04) per year were significantly lower in participants receiving blenderized diets, and respiratory ER visits trended toward significance (0.1±0.4 vs. 0.4±0.8, P=0.08). Compared with those receiving conventional formula, participants on blenderized diets reported higher satisfaction ratings (Likert scale 4.3 ± 1.0 vs 3.3 ± 1.2, P=0.001), lower symptom (0.7±0.8 vs. 1.2±1.1, P=0.03) and total (0.8±0.8 vs. 1.2±1.0, P=0.02) scores on PGSQ and higher scores on GI-PedsQL indicating less nausea and vomiting (64.0±22.6 vs. 49.0±37.9, P=0.02), abdominal pain (65.0±26.8 vs. 56.4±33.9, P=0.04), diarrhea (87.9±15.5 vs. 73.6±26.3, P=0.004) and fewer total symptoms (70.2±16.3 vs. 62.3±19.6, P=0.03). CONCLUSIONS: Blenderized diets are associated with decreased health care utilization, improved symptom scores and increased patient satisfaction compared with conventional formulas.